Perdas de alimentos na CEASA-GO à luz da teoria das ações coletivas - Rezende, Maryele Lázara (2023)
The food losses in the different stages of the production chain led to a reduction in the volume of food available to the population, generating significant social, economic and environmental consequences. CEASA-GO, along with other warehouses in Brazil, faces challenges related to food losses, which results in local problems, such as the accumulation of waste to be discarded, the attraction of waste pickers and economic loss for farmers and entrepreneurs who work in the warehouse. In this sense, this doctoral dissertation aims to evaluate the food losses that occur in CEASA-GO in the light of the theory of collective actions. Therefore, this thesis was structured in three articles that address the specific results of this work. The first article entitled "Food losses: bibliometric analysis" explores the literature on food losses through bibliometric analysis in the Web of Science and Scopus databases, and reveals that studies on food losses are relatively recent and that countries such as the USA and the European Union have taken the lead in research. In the qualitative analysis of the articles, the existence of eight categories of research on the subject was verified, namely: cause and prevention of losses; loss estimation; environmental impact; Packaging; logistics; food recovery; donation and conceptual aspects. In the second article entitled "Food losses and collective actions in CEASA-GO: an application of the logit model", the objective was to map the losses that occur in CEASA-GO through the application of structured questionnaires, analyzed in the logit model, and to evaluate whether the sociodemographic and behavioral differences of CEASA-GO users impact on the adoption of loss reduction strategies, It was found that younger traders, making donations to the food bank and participating in collective actions positively influenced these groups to adopt strategies to reduce food losses. The third article of this thesis "Collective actions and food losses: an analysis of CEASA-GO" sought to verify if there are collective actions in CEASA GO and if these cooperate with the reduction of food losses, for this purpose semi-structured interviews were conducted with associates and cooperative members of the two collective actions identified in the warehouse. These collective actions did not have as their initial objective to solve the problem of losses in the warehouse, but began to adopt strategies to reduce losses in the search for economic benefits or resolution of operational problems of the warehouse. The main activities developed by the collective actions to reduce food losses were the creation of the food bank, access to institutional marketing channels and maintenance of shared and refrigerated space to store goods. In a general analysis of the results of this thesis it is possible to affirm that collective actions contribute positively to the reduction of losses in CEASA-GO, since it is a joint action of agents that would not find strength and organization when carried out in individual and uncoordinated activities. The loss reduction actions developed by the collective actions contribute to an integral sustainable development by addressing actions that promote economic, social and environmental development to the agents that work in the warehouse and to CEASA-GO itself. Finally, this thesis contributes to studies on food losses by evaluating a link little explored in the literature. This research also contributes to the theory of collective actions by applying it in the context of agribusiness and evidencing that, for this analysis, large groups can perform more efficiently supported by online and fast communication. This study has practical relevance, providing a list of potential actions to reduce the generic losses in CEASA-GO.